Femto-assisted versus conventional phacoemulsification differently impact on choroid structure after surgery. Issue 4 (July 2022) - Appolloni, Romolo; Viggiano, Pasquale; Carrella, Maria Luisa; Evangelista, Federica; Appolloni, Alessandro; Toto, Lisa; Mastropasqua, Leonardo
Purpose: To report potential choroidal changes in eyes undergoing femtosecond laser cataract surgery (FLACS) and phacoemulsification surgery (PCS) by OCT. Methods: The patients were images by means Spectral Domain OCT imaging with EDI technology which may obtain OCT image. We exported a single EDI-OCT scan passing through the fovea and then it was imported into ImageJ program to perform a quantitative analysis. Main outcome measures: The main outcome measures were: (i) sub foveal choroidal thickness (SFCT); (ii) the choroidal vascularity index (CVI); and (iii) central retinal thickness (CRT). Results: At postoperative 1 week, FLACS group showed an increased CRT (241.2 ± 31.6–245.5 ± 36.4 µm; p  = 0.016). Likewise, CVI and SFCT exhibited a slight increase but no statistically differences were highlighted ( p  > 0.05). At the follow-up visit of 1 month, all OCT parameters did not display any significant difference ( p  > 0.05). At post-operative 1 week, the PCS group displayed a significant increase in CRT, SFCT, and CVI. On the contrary, at the follow-up visit of 1-month, all choroidal parameters were characterized by a no statistically significant reduction ( p  > 0.05). Conclusions: Our study exhibited a significant increase in CT and CVI in eyes that underwent conventional cataract surgery. Femtosecond laser-assisted cataract extraction did not result in macular change due to less postoperative inflammation.